ANALISIS EFEKTIVITAS DAN EFISIENSI PELAKSANAAN ANGGARAN BELANJA PADA BADAN PEMBERDAYAAN MASYARAKAT DAN PEMERINTAHAN DESA (BPMPD) DAERAH PROPINSI SULAWESI TENGAH - Basariyah, Siti (Katalogis, 2017)
This research is conducted in The Agency of Community Empowerment and Village Goverment of Central Sulawesi Province and aims to analyze the effectiveness and efficiency of budget execution and to identify contraints in budget execution in The Agency of community Empowerment and Village Goverment of Central Sulawesi Province with descriptive data analysis. Informants in this research are officials in The Agency of Community Empowerment and Village Goverment of Central sulawesi Province. The results identifie that the effectiveness ratio of programs from 2011 to 2015 in average had been high, means that programs effectively implemented. Yet, there were some programs in the year of 2013 and 2015 categorized “quite effective’ because some budgeted programs did not run very well. Efficiency ratio during that period of time shows that budget execution is quite efficient, especially in 2015. This means that programs are well executed despite some budget cuts; the minimum budgeting can produce good program performance.